Mandibular Atrophy and Genial Spines Enlargement on Cone Beam Computed Tomography - Marcelo Lupion Poleti; Christiano Oliveira-Santos; Luciana Maria Paes da Silva Ramos Fernandes; Izabel Regina Fischer Rubira-Bullen (Case Reports in Dentistry)
Purpose. The aim of this paper is to report a case in which the cone beam computed tomography (CBCT) was important for the confirmation of the presence of mandibular atrophy and genial spines enlargement. Case Description. A 76-year-old female patient was referred for the assessment due to the complaint of chronic trauma in the anterior region of the floor of the mouth, which had been present for 2 months. CBCT images showed severe resorption of alveolar ridge and genial spines enlargement (5.5 mm × 12 mm). Conclusion. Accurate imaging assessment with the aid of 3D reconstructions allows the elimination of image superimposition and, therefore, plays an important role in the depiction of anatomical and pathological conditions, such as genial spines enlargement.